Flipped learning, personality traits, and student outcomes: evidence from a controlled university trial - Dabaj, Tekin; İşman, Aytekin (Frontiers in Psychology, 2026)
This pilot controlled study (N = 42) compared flipped and traditional classroom instruction in a short university-level cryptography course and examined whether personality traits exhibit preliminary associations with students’ academic performance and engagement. Students in the flipped condition outperformed those in the traditional setting, reinforcing the documented instructional benefits of flipped learning. Although two group-specific correlations (conscientiousness in the flipped group and neuroticism in the traditional group) reached statistical significance, the small sample size limits the stability and generalizability of these effects; therefore, personality findings are interpreted as exploratory. The study contributes transparent methodology, reliable measures, and an instructional design model to support replication. Implications for practice, limitations, and recommendations for future research are discussed.